Internal versus external assessment in vocational qualifications: A commentary on the government's reforms in England (UCL Press, 2017)
The distinction between external assessment and internal assessment underpins a major reform to vocational qualifications underway in England. To be approved by the Department for Education, vocational qualifications must now include a minimum proportion of external assessment, regardless of subject. This paper discusses the nature and implications of this constraint on qualification design. First, it clarifies the meaning of external assessment and the key arguments underpinning the reform. Second, it evaluates the use and implementation of this blanket rule. The final section discusses the nature of internal assessment in more detail, highlighting its heterogeneity and potential advantages over external assessment.